Working with the Public: How an Unusual Museum Enquiry Turned into Travels Through Time and Space. (5th August 2015) - Freedman, Jan; Evans, Jane
Museum enquiries offer a unique opportunity to engage on a one-to-one level with members of the public. This paper covers an unusual enquiry from 2013 of an unknown tooth that was brought into Plymouth City Museum and Art Gallery for identification. We highlight how museum enquiries can engage with members of the public by involving them directly with original scientific research. The tooth was found in a garden in Plymouth with no associated data of about where it originated. We identified the tooth, and the enquirer researched the history of the house. The tooth gave the appearance of a sub-fossil so with the large number of Quaternary sites in Plymouth, together with the identification of the previous owner on the site, there were valid reasons to undertake testing of the tooth to determine its origin. Strontium (Sr) isotope analysis of the tooth was carried out to determine if the tooth was British and radiocarbon dating was undertaken to work out the age of the tooth. The 87 Sr / 86 Sr of the leopard tooth gave a value of 0.716131, with Sr concentrations at 568ppm. This is a high concentration of Sr ppm relative to other British data, suggesting a non-British origin. The radiocarbon measurement was 187 ± 24 years BP (University of Oxford Radiocarbon Accelerator Unit reference OxA-30390). This places the tooth not in the Pleistocene, but between 1739 and 1787 AD. The site where the tooth was discovered was owned by the brother of Linnaeus Tripe who travelled across India and Burma. We argue that the results of this study demonstrate that this leopard tooth was originally from India or Burma, and brought into Britain by Tripe. A correction article relating to the radiocarbon dates included in this publication can be found here:http://dx.doi.org/10.5334/oq.aj